Ultra-high strength Al-Zn-Mg-Cu alloy with Er and Zr composite addition and its preparation process

By adding Er and Zr elements to the Al-Zn-Mg-Cu alloy and using a specific process to form dispersion and precipitation of Al3 (Er, Zr) particles, the shortcomings of the alloy in terms of peeling corrosion resistance and manufacturing cost are solved. , achieves ultra-high strength and excellent corrosion resistance, while reducing energy consumption.

CN116219240BActive Publication Date: 2025-02-14BEIJING UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310228661.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-03
Publication Date
2025-02-14
Estimated Expiration
2043-03-03

AI Technical Summary

Technical Problem

There is still room for improvement in the performance and cost of existing Al-Zn-Mg-Cu alloys, especially in terms of peeling corrosion resistance and manufacturing costs.

Method used

By adding Er and Zr elements to the Al-Zn-Mg-Cu alloy, and using three-stage homogenization system, hot extrusion deformation, solid solution treatment and three-stage aging treatment, Al3(Er, Zr) particles are formed. Dispersed and precipitated to optimize the microstructure of the alloy.

Benefits of technology

The ultra-high strength of the alloy and excellent anti-flaking corrosion performance are achieved, while reducing manufacturing costs and reducing energy losses through high-temperature short-term treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116219240B_ABST
    Figure CN116219240B_ABST
Patent Text Reader

Abstract

Ultra-high-strength Al-Zn-Mg-Cu alloy with Er and Zr composite addition and preparation process, the composition is Zn7.4-8.1wt.%, Mg2.2-2.6wt.%, Cu0.8-1.2wt.%, Mn0.2-0.5wt.%, Er0.02-0.20wt.%, Zr0.05-015wt.%, the balance is Al and inevitable impurities. Pure aluminum, pure zinc, pure magnesium, Cu plate, Al-Mn, Al-Zr, Al-Er ingredients are used; Mg, Cu, Zn are added in the form of pure metals, and Zr and Er are added in the form of intermediate alloys to complete ingot smelting. In order to eliminate the segregation of cast structure, improve the uniformity of alloy structure, and promote the dispersion and precipitation of Al3 (Er, Zr) particles in the alloy, three-level homogenization treatment is carried out: 350℃ / 8h+420℃ / 4h+480℃ / 8h; 450℃ extrusion into thick-walled pipes; for the dispersion and precipitation of precipitated phases, 470℃ / 2h solid solution treatment is carried out, water cooling is carried out to increase the supersaturation of the alloy; 120℃ / 16h+180℃ / Xmin+120℃ / 20h, 120℃ / 16h+190℃ / Xmin+120℃ / 20h three-level regression and aging. The three-level regression and aging treatment ensures the strength of the alloy and improves the corrosion resistance of the alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aluminum alloy material and a preparation process thereof, and in particular to an ultra-high strength Al-Zn-Mg-Cu alloy and a preparation process thereof. Background Art

[0002] Al-Zn-Mg-Cu alloy has the advantages of high specific strength, high fracture toughness, excellent welding performance and fatigue resistance, so it has been widely used in the fields of construction, vehicles, aerospace, etc. In order to meet the needs of engineering applications, Al-Zn-Mg-Cu alloy is gradually developing towards ultra-high strength. As an aluminum alloy that can be strengthened by heat treatment, the dispersed precipitation phase of Al-Zn-Mg-Cu alloy will affect the performance of Al-Zn-Mg-Cu alloy. With the research on alloy properties, different aging systems have also emerged. According to the different performance requirements of the alloy, different microstructures are formed, which in turn affect the performance of the alloy.

[0003] It is desirable in the art to obtain Al-Zn-Mg-Cu alloys with better performance and lower cost. Summary of the invention

[0004] The purpose of the present invention is to provide an Al-Zn-Mg-Cu alloy and a preparation method thereof, so that the alloy not only has ultra-high strength, but also has good anti-exfoliation corrosion performance and lower manufacturing cost.

[0005] Therefore, the present invention provides an ultra-high strength Al-Zn-Mg-Cu alloy with composite additions of Er and Zr, wherein the alloy composition is Zn 7.4-8.1wt.%, Mg 2.2-2.6wt.%, Cu 0.8-1.2wt.%, Mn 0.2-0.5wt.%, Er 0.02-0.20wt.%, Zr 0.05-015wt.%, and the balance is Al and unavoidable impurities.

[0006] As a preferred method, the alloy composition is Zn: 8.1wt.%, Mg: 2.4wt.%, Cu: 1.1wt.%, Mn: 0.3wt.%, Er: 0.088wt.%, Zr: 0.092wt.%, and the remainder is Al and inevitable impurities; to ensure that the Fe and Si impurity contents meet the process control requirements, Al99.70% aluminum ingots with higher purity (lower Fe and Si impurity contents) are selected to match some high-precision aluminum ingredients; Mg, Cu, and Zn are added in the form of pure metals, and Zr and Er are added in the form of intermediate alloys Al-Zr and Al-Er, respectively, to ensure that the primary waste does not exceed 40%, thereby ensuring the stability and consistency of alloy element control.

[0007] On the other hand, the present invention provides a method for preparing the aforementioned alloy, which comprises the following steps: (1) using a resistance heating furnace to melt the alloy at a temperature of 800±10°C, firstly putting high-purity aluminum into a crucible, keeping it warm in a resistance furnace, and adding other metals after it is completely melted and keeping warm. Mg, Cu, and Zn are added in the form of pure metals, and Zr and Er are added in the form of intermediate alloys Al-Zr and Al-Er, respectively, to ensure that the primary waste does not exceed 40%, and to ensure the stability and consistency of the alloy element control. Since the Er element has a large specific gravity, in order to prevent segregation during the smelting process, the Al-Er intermediate alloy and Mg are directly added to the aluminum liquid at 740°C to 760°C, and the Ar+Cl in the furnace is used. 2 And online Ar degassing scheme to complete alloy smelting and casting. (2) The ingot obtained in step (1) is subjected to homogenization treatment at 350℃ / 10h+470℃ / 24h, 350℃ / 8h+420℃ / 4h+480℃ / 8h, and water-cooled to room temperature. (3) The alloy obtained in step (2) is extruded at 450℃, with an extrusion coefficient of 5.5 and an extrusion speed of 0.5m / min. (4) The alloy obtained in step (3) is solution treated at 470℃ / 2h, the heating process is 4h, and it is water-cooled to room temperature. (5) The alloy obtained in step (4) is subjected to three-level regression and re-aging at 120℃ / 16h+180℃ / Xmin+120℃ / 20h, 120℃ / 16h+190℃ / Xmin+120℃ / 20h.

[0008] The first stage of the three-stage homogenization system provided by the present invention is 350°C, which can ensure that Al 3 (Er, Zr) particles are dispersed and precipitated, and the second and third temperature are 420℃ and 480℃ respectively, which can basically eliminate the element segregation in the cast structure and make the alloy composition evenly distributed. At the same time, the high temperature and short time system can shorten the homogenization time; the hot extrusion process ensures that the extrusion deformation has no obvious defects; the solid solution and three-level aging treatment can make the alloy have a higher supersaturation and a higher nucleation driving force. At the same time, the number of precipitated phases in the crystal is large and dispersed, and the precipitated phases at the grain boundaries are discontinuously distributed. It has ultra-high strength and excellent anti-exfoliation corrosion performance.

[0009] The three-stage aging treatment system can ensure high strength while improving the corrosion resistance of the alloy. At the same time, after adding micro-alloying elements Er and Zr to the Al-Zn-Mg-Cu alloy, the Al 3 (Er, Zr) particles, dispersed fine Al 3 (Er, Zr) particles can pin the grain boundaries during grain growth, thereby inhibiting grain growth. Based on this technology, the present invention designs a homogenization system and a three-stage aging treatment system suitable for the ultra-high strength Al-Zn-Mg-Cu alloy with composite additions of Er and Zr.

[0010] The present invention has the following positive effects:

[0011] The three-stage homogenization system provided by the present invention not only eliminates the defects of the as-cast structure, but also ensures that the Al 3 (Er, Zr) particles are dispersed and precipitated, and alloy recrystallization is inhibited during the subsequent heat treatment process. At the same time, high-temperature short-time treatment reduces energy loss; extrusion deformation can remove the voids after homogenization treatment and refine the grains; solid solution and three-level aging treatment make the alloy adapt to the strength and corrosion relationship to meet application requirements. The present invention prepares the alloy by microalloying Er and Zr elements on Al-Zn-Mg-Cu alloy and changing its homogenization and aging system, so that the alloy has ultra-high strength and good corrosion resistance.

[0012] The ultra-high strength Al-Zn-Mg-Cu alloy preparation method of the present invention adopts a three-stage homogenization system, extrusion deformation, solution treatment, and three-stage aging treatment to form a unified and complete whole, and uses the specific process parameters that have been explored with great difficulty to achieve that the Al-Zn-Mg-Cu alloy has both ultra-high strength and good corrosion resistance. What is particularly valuable is that it can reduce energy loss and manufacturing costs through high-temperature short-time treatment. Although the three-stage aging system loses less strength, it improves the corrosion performance of the alloy, thereby achieving ultra-high strength and corrosion matching. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is the SEM image of the alloy cast structure.

[0014] Figure 2(a) is the SEM image of the alloy after double-stage homogenization at 350℃ / 10h+470℃ / 24h.

[0015] Figure 2(b) shows the Al alloy after double-stage homogenization at 350℃ / 10h+470℃ / 24h. 3 TEM image of (Er,Zr) phase.

[0016] Figure 3(a) is the SEM image of the alloy after three-stage homogenization at 350℃ / 8h+420℃ / 4h+480℃ / 8h.

[0017] Figure 3(b) shows the Al content of the alloy after three-stage homogenization at 350℃ / 8h+420℃ / 4h+480℃ / 8h. 3 TEM image of (Er,Zr) phase.

[0018] Figure 4 These are the aging hardness change curves of the alloy at 120℃ / 16h+180℃ / Xmin+120℃ / 20h and 120℃ / 16h+190℃ / Xmin+120℃ / 20h.

[0019] Figure 5 Alloy 120℃ / 16h+180℃ / Xmin+120℃ / 20h, 120℃ / 16h+190℃

[0020] / Xmin+120℃ / 20h effective time mechanical properties and exfoliation corrosion grade table. DETAILED DESCRIPTION

[0021] Hereinafter, an embodiment of an ultra-high strength Al-Zn-Mg-Cu alloy with Er and Zr added thereto and a preparation process thereof according to the present invention will be described with reference to the accompanying drawings.

[0022] The embodiments described herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention, are illustrative and exemplary, and should not be interpreted as limiting the embodiments of the present invention and the scope of the present invention. In addition to the embodiments described herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims and the specification of this application, including any obvious replacement and modification of the embodiments described herein.

[0023] In this embodiment, the alloy composition is determined to be Zn: 8.1wt.%, Mg: 2.4wt.%, Cu: 1.1wt.%, Mn: 0.3wt.%, Er: 0.088wt.%, Zr: 0.092wt.%, and the remainder is Al and unavoidable impurities.

[0024] In order to ensure that the impurity content of Fe and Si meets the process control requirements, Al99.70% aluminum ingots with higher purity are selected and matched with some high-precision aluminum ingredients. The impurity content of Fe and Si in Al99.70% aluminum ingots with higher purity is lower.

[0025] Mg, Cu, and Zn are added in the form of pure metals, and Zr and Er are added in the form of master alloys Al-Zr and Al-Er, respectively, to ensure the stability and consistency of alloy element control. Mn can also be added in the form of master alloy Al-Mn.

[0026] The following describes the method for preparing the above alloy and the corresponding comparative experiments.

[0027] Step (1): Use a resistance heating furnace to melt the alloy at a temperature of 800±10℃. First, put high-purity aluminum into a crucible and keep it warm in a resistance furnace. After it is completely melted, add other metals and keep them warm. Mg, Cu, and Zn are added in the form of pure metals, and Zr and Er are added in the form of intermediate alloys Al-Zr and Al-Er, respectively. Ensure that the primary waste does not exceed 40% to ensure the stability and consistency of alloy element control. Due to the large specific gravity of the Er element, in order to prevent segregation during the smelting process, the Al-Er intermediate alloy and Mg are directly added to the aluminum liquid at 740℃~760℃ at the same time, and Ar+Cl in the furnace is used. 2 And online Ar degassing solution to complete alloy melting and casting. Figure 1 As shown in the figure, the primary phase is continuously distributed at the grain boundaries, which easily causes cracks at the grain boundaries and affects the properties of the alloy.

[0028] Preferably, Mn is added in the form of a master alloy Al-Mn.

[0029] Step (2): Place the ingot obtained in step (1) in a resistance furnace and heat it to 350°C, keep it warm for 10 hours; then heat it to 470°C, keep it warm for 24 hours, perform a two-stage homogenization treatment, the heating rate is 10° / min, and water cool it to room temperature; observe the microstructure of the alloy by combining SEM and TEM. From Figure 2(a), it can be seen that the non-equilibrium eutectic phase at the grain boundary is basically eliminated, and the remaining insoluble phase has a high melting point and cannot be eliminated; from Figure 2(b), it can be seen that during the two-stage homogenization process, Al 3 (Er, Zr) particles are dispersed and precipitated.

[0030] Comparison step (2)

[0031] The ingot obtained in step (1) was placed in a furnace and heated to 350°C, kept warm for 8 hours; then heated to 420°C, kept warm for 4 hours, and finally heated to 480°C, kept warm for 8 hours for three-stage homogenization treatment, with a heating rate of 10° / min, and water-cooled to room temperature; as in step 2, the microstructure of the alloy was observed by SEM and TEM. The results were basically the same as those of the two-stage homogenization system. Figure 3(a) and 3(b) It can be seen that the non-equilibrium eutectic phase is basically eliminated, and Al 3 (Er, Zr) particles were also fully precipitated.

[0032] The microstructures of step (2) of Example 1 and step (2) of the comparative example are compared. The results show that the two-stage homogenization treatment of 350℃ / 10h+470℃ / 24h and the three-stage homogenization treatment of 350℃ / 8h+420℃ / 4h+480℃ / 8h can basically eliminate the non-equilibrium eutectic phase of the ingot structure and effectively promote the Al 3(Er, Zr) particles are dispersed and precipitated; however, the three-level homogenization system adopts high temperature and short time treatment, which shortens the homogenization treatment time and reduces energy loss.

[0033] Step (3): The alloy obtained in step (2) is subjected to hot extrusion deformation, with an extrusion coefficient of 5.5 and an extrusion speed of 0.5 m / min, and no obvious cracking phenomenon is observed, and the alloy is extruded into a thick-walled tube. Extrusion deformation can remove the voids after homogenization treatment, eliminate cracking, and refine the grains, thereby improving strength and toughness.

[0034] Step (4): The thick-walled pipe obtained in step (3) is subjected to wire cutting to obtain a small-size sample, which is placed in a resistance furnace and heated to 470°C, kept at this temperature for 2 hours, and the heating process is 4 hours, and then water-cooled to room temperature for solution treatment. The solution treatment is combined with the subsequent three-stage aging treatment to make the alloy adapt to the strength and corrosion relationship and meet the application requirements.

[0035] Step (5): The alloy obtained in step (4) is subjected to three-stage regression and re-aging treatment, wherein the first stage is kept at 120°C for 16 hours; the second stage is treated at 180°C and 190°C for 0 to 180 minutes; and the third stage is kept at 120°C for 20 hours. The alloy subjected to three-stage aging is subjected to Vickers hardness test, room temperature tensile test, exfoliation corrosion test, and SEM and TEM microstructure characterization. The room temperature tensile test is carried out in accordance with the standard "Metallic Materials-Tensile Test" (GB / T 228.1-202×), and the exfoliation corrosion test is carried out in accordance with the standard "Exfoliation Corrosion Test Method for Aluminum Alloy Processing Products" (GB / T 22639-2008).

[0036] Figure 4 The three-level aging hardness change curves of the alloy are 120℃ / 16h+180℃ / Xmin+120℃ / 20h and 120℃ / 16h+190℃ / Xmin+120℃ / 20h. From the figure, it can be seen that the peak aging hardness of 120℃ / 16h+180℃ / Xmin+120℃ / 20h and 120℃ / 16h+190℃ / Xmin+120℃ / 20h are similar. The peak hardness at the regression temperature of 180℃ is 207HV, and the peak aging time is 40min; the hardness at the regression temperature of 190℃ is 207HV, and the aging time is 30min. The peak hardness is reached faster at the regression temperature of 190℃ than at 180℃; the overall hardness change curves at the regression temperatures of 180℃ and 190℃ are both rising first and then falling.

[0037] See also Figure 5, which shows the experimentally obtained aging mechanical properties and exfoliation corrosion grade table of the alloy at 120℃ / 16h+180℃ / Xmin+120℃ / 20h, 120℃ / 16h+190℃ / Xmin+120℃ / 20h. From the figure, we can see that as the regression time increases, the overall strength of the alloy gradually decreases, and the exfoliation corrosion resistance is improved; the tensile strength is above 593MPa, the yield strength is above 568MPa, the elongation is above 11%, and the corrosion grade is above EA. The aging system is 120℃ / 16h+180℃ / 60min+120℃ / 20h, 120℃ / 16h+190℃ / 60min+120℃ / 20h, the alloy has both ultra-high strength and improved corrosion resistance.

[0038] The experimental results show that the three-level homogenization system and the three-level regression re-aging system provided by the present invention both make the alloy present excellent comprehensive properties. The first level of the three-level homogenization system is 350℃, which can effectively promote the Al 3 (Er, Zr) particles are dispersed and precipitated, which inhibits alloy recrystallization during heat treatment, making the alloy have more substructures and tortuous grain boundaries, improving the corrosion resistance of the alloy; the second and third levels of 420℃ and 480℃ can basically eliminate the non-equilibrium eutectic phase of the ingot and prevent the alloy from extrusion deformation and cracking; the three-level homogenization system uses high-temperature short-time treatment, which shortens the homogenization treatment time and reduces energy loss, which is more excellent in the current green development. The three-level aging system improves the corrosion resistance of the alloy while losing less strength, achieving ultra-high strength and corrosion matching.

[0039] The three-stage homogenization system provided by the present invention not only eliminates the defects of the as-cast structure, but also ensures that the Al 3 (Er, Zr) particles are dispersed and precipitated, which inhibits the recrystallization of the alloy during the subsequent heat treatment process, and high-temperature short-time treatment reduces energy loss; extrusion deformation can remove the voids after homogenization treatment, refine the grains, and improve strength and toughness; solid solution and three-level aging treatment can make the alloy have a higher supersaturation and a higher nucleation driving force. At the same time, the number of precipitated phases in the crystal is large and dispersed, and the precipitated phases at the grain boundaries are discontinuously distributed. It has ultra-high strength and excellent anti-exfoliation corrosion performance, so that the alloy adapts to the strength and corrosion relationship to meet application requirements.

[0040] Please note that the three-stage homogenization system, extrusion deformation, solution treatment, and three-stage aging treatment used in the ultra-high strength Al-Zn-Mg-Cu alloy preparation method of the present invention are not a random combination that is easily obtained, but an organic combination obtained by the inventor after in-depth research and long-term experiments. Such an organic combination forms a unified and complete whole, and uses the specific process parameters that have been explored with great difficulty to achieve Al-Zn-Mg-Cu alloys that have both ultra-high strength and good corrosion resistance. What is particularly valuable is that it can reduce energy loss and manufacturing costs through high-temperature short-time treatment. In order to solve the problem that the corrosion resistance of Al-Zn-Mg-Cu alloys is still not ideal, the preparation method of the present invention loses less strength through the three-stage aging system, but achieves matching ultra-high strength with corrosion, thereby creatively proposing a new means to solve existing defects.

[0041] The above is a description of the implementation method of an ultra-high strength Al-Zn-Mg-Cu alloy with composite additions of Er and Zr and its preparation process of the present invention, the purpose of which is to explain the spirit of the present invention. The specific features of the preparation process of the present invention can be specifically designed according to the effects of the features disclosed above, and these designs can be implemented by those skilled in the art. Moreover, the various technical features disclosed above are not limited to the combination with other features disclosed, and those skilled in the art can also make other combinations between the various technical features according to the purpose of the present invention, so as to achieve the purpose of the present invention.

Claims

1. An ultra-high strength Al-Zn-Mg-Cu alloy with Er and Zr added, characterized in that: Alloy composition: Zn: 8.1wt.%, Mg: 2.4wt.%, Cu: 1.1wt.%, Mn: 0.3wt.%, Er: 0.088wt.%, Zr: 0.092wt.%, the remainder is Al and inevitable impurities; to ensure that the impurity content of Fe and Si meets the process control requirements, Al99.70% aluminum ingots with higher purity are selected to match some high-precision aluminum ingredients; Mg, Cu, and Zn are added in the form of pure metals, and Zr and Er are added in the form of intermediate alloys Al-Zr and Al-Er, respectively, to ensure that the primary waste does not exceed 40%, and to ensure the stability and consistency of alloy element control, wherein the ultra-high strength Al-Zn-Mg-Cu alloy has undergone three-stage homogenization treatment at 350℃ / 10h+470℃ / 24h, 350℃ / 8h+420℃ / 4h+480℃ / 8h and 120℃ / 16h+180℃ / Xmin +120℃ / 20h , 120℃ / 16h+190℃ / Xmin+120℃ / 20h three-stage regression aging, among which, 0 <X≤180。 2. The ultra-high strength Al-Zn-Mg-Cu alloy with Er and Zr added as claimed in claim 1, characterized in that: Mn is added in the form of a master alloy Al-Mn.

3. A method for preparing the alloy according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) The alloy is melted at 800±10℃ in a resistance heating furnace. First, high-purity aluminum is placed in a crucible and kept warm in a resistance furnace. After it is completely melted, other metals are added and kept warm. Mg, Cu, and Zn are added in the form of pure metals, and Zr and Er are added in the form of intermediate alloys Al-Zr and Al-Er, respectively, to ensure that the primary scrap does not exceed 40%. In order to prevent segregation during the melting process due to the high specific gravity of the Er element, the Al-Er intermediate alloy and Mg are directly added to the aluminum liquid at 740℃~760℃. At the same time, the furnace Ar+Cl2 and online Ar degassing schemes are used to complete the alloy melting and casting. (2) subjecting the alloy obtained in step (1) to a three-stage homogenization treatment at 350°C / 10h+470°C / 24h, 350°C / 8h+420°C / 4h+480°C / 8h, and water cooling to room temperature; (3) Extruding the alloy obtained in step (2) at 450° C., with an extrusion coefficient of 5.5 and an extrusion speed of 0.5 m / min; (4) subjecting the alloy obtained in step (3) to a solution treatment at 470°C for 2 h, with the heating process lasting 4 h, and then cooling to room temperature with water; (5) The alloy obtained in step (4) is subjected to three-stage regression aging at 120°C / 16h+180°C / Xmin+120°C / 20h and 120°C / 16h+190°C / Xmin+120°C / 20h, wherein 0 <X≤180。 4. The method according to claim 3, characterized in that In step (1), Mn is added in the form of a master alloy Al-Mn.

Citation Information

Patent Citations

  • Homogenizing heat treatment process of Er and Zr composite microalloyed Al-Zn-Mg-Cu alloy

    CN104451291A

  • 800MPa-level ultrahigh-strength aluminum alloy and preparing method thereof

    CN106399776A

  • Ultrahigh-toughness cast aluminum alloy and forming method thereof

    CN114457266A